Virus‐Inspired Hollow Mesoporous Gadolinium‐Bismuth Nanotheranostics for Magnetic Resonance Imaging‐Guided Synergistic Photodynamic‐Radiotherapy. Issue 6 (19th December 2021) - Liu, Zongjunlin; Wang, Peiyuan; Xie, Fang; Chen, Jianhao; Cai, Meimei; Li, Yang; Yan, Jianghua; Lin, Qin; Luo, Fanghong
Abstract: The anti‐tumor efficacy of single photodynamic therapy (PDT) and radiotherapy (RT) has been greatly affected by inadequate tumor uptake of photo/radiation sensitizers, limited laser penetration depth, and radiation sickness caused by high doses of X‐rays. Here, the authors report a biomimetic coronavirus‐inspired hollow mesoporous gadolinium/bismuth nanocarrier loaded with a new NIR photosensitizer HB (termed as HB@VHMBi‐Gd) for magnetic resonance imaging (MRI)‐guided synergistic photodynamic‐RT. HB@VHMBi‐Gd displayed a faster cellular uptake rate than the conventional spherical HMBi‐Gd loaded with HB (HB@SHMBi‐Gd) because of rough surface‐enhanced adhesion. After intravenous injection, HB@VHMBi‐Gd is efficiently delivered to the tumor and rapidly invades the tumor cells by surface spikes. Interestingly, lysosomal acidity can trigger the degradation of VHMBi‐Gd to produce ultrasmall nanoparticles to amplify the X‐ray attenuation ability and enhance MRI contrast and radiosensitization. Under laser and X‐ray irradiation, HB@VHMBi‐Gd significantly enhances 1 O2 generation from HB to induce activation of caspase 9/3 and inhibition of C‐myc, while enhancing hydroxyl radical generation from Bi2 O3 to induce intense DNA breakage. By synergistically inducing cell apoptosis by distinct reactive oxygen species (ROS), HB@VHMBi‐Gd exhibits superior anticancer efficacy with ≈90% tumor inhibition. They envision that biomimetic virus‐inspired hollow hybrid metal nanoparticles can provide a promising strategy for imaging‐guided synergistic photodynamic‐RT. Abstract : A novel biomimetic coronavirus‐inspired hollow mesoporous gadolinium/bismuth nanocarrier loaded with photosensitizer HB for powerful tumor cell invasion and MR imaging‐guided synergistic photodynamic‐radiotherapy is constructed. Under laser and X‐ray irradiation, HB@VHMBi‐Gd significantly enhanced 1 O2 generation from HB to induce activation of caspase 9/3 and inhibition of C‐myc, while enhancing hydroxyl radical generation from Bi2 O3 to induce intense DNA breakage.